2022
DOI: 10.1155/2022/7616696
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal CXCL14 Contributes to M2 Macrophage Polarization through NF-κB Signaling in Prostate Cancer

Abstract: Chemokine (C-X-C motif) ligand 14 (CXCL14) plays a critical role in maintaining homeostasis and inflammation in the local cell environment and regulating cancer progression. However, the role of CXCL14 in prostate cancer (PC) has not been fully investigated. In this study, the expression of CXCL14 was determined in PC tumor tissues by qRT-PCR and immunohistochemistry assay. Wound healing, invasion, colony formation, cell proliferation, and apoptosis assays were performed to evaluate the role of CXCL14 in PC pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Interestingly, we found that the regulation of M2 macrophage polarization by platelets in the tumor microenvironment was not unique to BLCA; it was also observed in renal cancer cells but not in prostate cancer cells. Previous studies have reported that the renal cancer microenvironment promotes the polarization of M2 macrophages, 21 whereas prostate cancer polarizes macrophages in favor of M1 macrophages, 22 which is consistent with our experimental results; however, an opposing view has been published 23 . Our experimental results provide evidence to clarify this controversial issue from the perspective of platelet involvement.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, we found that the regulation of M2 macrophage polarization by platelets in the tumor microenvironment was not unique to BLCA; it was also observed in renal cancer cells but not in prostate cancer cells. Previous studies have reported that the renal cancer microenvironment promotes the polarization of M2 macrophages, 21 whereas prostate cancer polarizes macrophages in favor of M1 macrophages, 22 which is consistent with our experimental results; however, an opposing view has been published 23 . Our experimental results provide evidence to clarify this controversial issue from the perspective of platelet involvement.…”
Section: Discussionsupporting
confidence: 91%
“…however, an opposing view has been published. 23 Our experimental results provide evidence to clarify this controversial issue from the perspective of platelet involvement.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…5 ). Although it did not impact PCa cell death, its downregulation prevented PCa cells from proliferating and invading [ 226 ]. Additionally, CXCL14 knockdown suppressed tumor growth in vivo.…”
Section: Chemokines/cxcrs and Pcamentioning
confidence: 99%
“…Emerging evidence underscores that the transition of M1 to M2 macrophages can reprogram the macrophage landscape, activating malignant processes within cancer cells by shaping the tumor microenvironment. For instance, exosomal FGD5-AS1 has been shown to stimulate cell proliferation and migration in pancreatic cancer by promoting M2 polarization of TAMs [12] , while exosome-delivered CXCL14 induces M2 polarization of TAMs, fostering prostate cancer progression [13] . Previous studies have established that exosomes mediate the transfer of RNA or proteins to adjacent cells or tissues, orchestrating alterations in the tumor microenvironment and driving tumor progression [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%